N- and C-terminal residues combine in the fusion-pH influenza hemagglutinin HA(2) subunit to form an N cap that terminates the triple-stranded coiled coil - Chen, Jue (The National Academy of Sciences, 1999)
The structure of a stable recombinant ectodomain of influenza hemagglutinin HA(2) subunit, EHA(2) (23–185), defined by proteolysis studies of the intact bacterial-expressed ectodomain, was determined to 1.9-Å resolution by using x-ray crystallography. The structure reveals a domain composed of N- and C-terminal residues that form an N cap terminating both the N-terminal α-helix and the central coiled coil. The N cap is formed by a conserved sequence, and part of it is found in the neutral pH conformation of HA. The C-terminal 23 residues of the ectodomain form a 72-Å long nonhelical structure ordered to within 7 residues of the transmembrane anchor. The structure implies that continuous α helices are not required for membrane fusion at either the N or C termini. The difference in stability between recombinant molecules with and without the N cap sequences suggests that additional free energy for membrane fusion may become available after the formation of the central triple-stranded coiled coil and insertion of the fusion peptide into the target membrane.